The effect of differentiated learning strategy on learning some types of handball scoring (Journal of the College of Basic Education, 2024)
The differentiated learning strategy is one of the strategies that center around the learner and takes into account the learner's experiences and takes into account the individual differences among the learners. The importance of the research is represented in the use of the differentiated learning strategy as it is a response to the learners' abilities. The use of differentiated learning in learning some types of handball scoring in addition to the goals and hypotheses. The second chapter includes the methodology and the research sample, and it was represented by the students of the Department of Physical Education in the College of Basic Education In addition to the research tests, the pre-tests, the implementation of the educational curriculum, the post-tests, and the research statistics. The third chapter included the results of the research, where one of the most important results was the superiority of the experimental group over the control group. The fourth chapter included the most important conclusions and recommendations. One of the most important recommendations is the need to use differentiated learning in learning some Types of handball scoring